Seeing animals after Derrida - Bezan, Sarah, 1986-; Tink, James, 1970- (Ecocritical theory and practice., 2018)
"Seeing Animals after Derrida marks a shift in studies of visuality in animal philosophy. Presenting an emergent set of questions for animal studies scholars, this volume intervenes in recent debates of the nonhuman turn that have been incited in the wake of a post-deconstructionist era"--